Characterization of polyanilineAgrGO nanocomposites for saprophytic and pathogenic Leptospira bacteria detection in water - Abdullah H.; Mahalingam S.; Azami N.H.; Bejo S.K.; Kamal N.; Othman M.H.D.; Yuliarto B.; Yahya I.; Manap A.; Fatihah S.; Abd Rahman N.; Yuhana N.Y.; et al. (Springer Science and Business Media Deutschland GmbH, 2024)
This research aims to develop polyaniline (PANI)AgrGO nanocomposite thin films to detect Saprophytic and Pathogenic Leptospira bacterias in water. The solgel method followed by a spin-coating technique was conducted in this work to synthesize nanocomposite thin films of PANIAg(1?x) rGOx (x = 0.025, 0.050, 0.075, 0.100). The results revealed that PANIAg0.975rGO0.025 thin film exhibited the most robust sensitivity, with the highest Ag concentration. The x-ray diffraction and field-emission scanning electron microscope analysis confirmed the structure of the nanocomposites with Ag nanospheres. The atomic force microscope study showed greater surface roughness for the nanocomposites with high Ag concentrations. Furthermore, PANIAg0.975rGO0.025 nanocomposite possessed the highest electrical conductivity (2.81 Scm?1), which resulted in the excellent detection of Leptospira bacteria in water. 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.